An Analysis On English Textbook Entitled Stairway: A Fun And Easy English Book For Grade II Of Elementary School Based On Rajan's Theory - Rosari, Dwi Vianita; , Drs. Djoko Srijono, M.Hum; , Dr. Dwi Haryanti, M.Hum (2014)
This research paper is mainly intended to find out whether the English textbook used for the second year students of Elementary school entitled Stairway: A Fun and Easy English Book is compatible or not with the indicators of good materials design suggested by Sundara Rajan. This research applies descriptive research. In collecting data, the writer did content analysis. The data were analyzed by (1) presenting the materials, (2) comparing the materials, (3) judging whether materials of English textbook appropriate with the indicators of good materials design suggested by Sundara Rajan or not, and (4) drawing conclusions. The result of the analysis shows that the English Textbook is compatible with the indicators of good materials design suggested by Rajan. The percentage of the compatibility of language skills developed in the textbook is 65,90% it means the textbook is good in developing language skills materials as suggested by Rajan. The language skill which are developed in the textbook involve the compatibility of the listening materials are 72,72% or good, the compatibility of the reading materials are 63,63% or good, the compatibility of speaking materials are 63,63% or good and the compatibility of writing materials are 63,63% or good. This research implies the textbook entitled Stairway: A Fun and Easy English Book is good materials to support the learning process.